How Much Does Latin America Gain from Enhanced Cross-Border Electricity Trade in the Short Run? - Timilsina, Govinda (World Bank, Washington, DC, 2021)
Regional or cross-border trade of electricity would be beneficial for all trading partners for multiple reasons. However, cross-border electricity trade in Latin America is limited, and the potential benefits have been forfeited. This study estimates the potential savings on electricity supply costs if 20 Latin American countries allowed unrestricted trade of electricity between the borders without expanding their current electricity generation capacity. Two hypothetical electricity trade scenarios—unconstrained trade of electricity between the countries within the Andean, Central, and Mercosur subregions and full regional trade involving all 20 countries are simulated using a power system model. The study shows that the volume of cross-border electricity trade would increase by 13 and 29 percent under the subregional and regional scenarios, respectively. The region would gain US$1.5 billion annually under the subregional scenario and almost US$2 billion under the full regional scenario. More than half of this gain would be realized by the Andean subregion under both scenarios. These are short-term benefits without expanding the current electricity generation capacities. In the future, when countries add more generation capacity to meet their increasing demand, the potential benefits of electricity trade would be higher. A further study is needed to measure the increased benefits in the long run.